The Mediating Effect of Job Satisfaction on Leadership Style & Turnover Intention Relationship - B. Yakoob, Najwa (Opción, 2019)
This study aims at investigating the relationship between leadership style, job satisfaction and turnover intention. The study also examined the mediating effect of job satisfaction on the relationship between leadership style and turn- over intention. Descriptive method was used to answer the hypotheses and questions of the study. The sample of the study consisted of employees at Al Thiqa private bank in Baghdad. A self-administered questionnaire was distributed to (40) respondents who constituted the community of the study. The Statistical Package for Social Sciences (SPSS version 23) was used to analyze the obtained data. The study concluded that a) there is a positive and signif- icant association between leadership style and job satisfaction. B) There is a negative and significant association between job satisfaction and turnover intention. C) There is a negative and significant association between leadership style and turnover intention. D) The effect of leadership style on turnover intention is increased by the mediating of job satisfaction. Also the study concluded that democratic leadership achieved the highest mean which indicated that it is the most dominant style of leadership among sample respondents.